2021
DOI: 10.3390/atmos12081026
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Enhanced Heatwaves over Tanzania and Scenario Projection in the 21st Century

Abstract: Extreme hot temperature is dangerous to the bioeconomy, and would worsen with time. Ambient heatwaves accompanied by unusual droughts are major threats to poverty eradication in Tanzania. Due to sparsity of observation data and proper heatwave detection metrics, there has been a paucity of knowledge about heatwave events in Tanzania. In this study, the Heatwave Magnitude Index daily (HWMId) was adopted to quantitatively analyze heatwave characteristics throughout Tanzania at mid-21st century (2041–2070) and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…13 (13%) of the articles cited in this review utilised reanalysis and climate models to simulate past, present, and future heat-human health relationships. 5 (5%) of studies explored future projections of heat stress, high temperature, relative humidity, heatwaves, and extreme heat on human health (Ermert et al 2012 ; Sylla et al 2018 ; Sarr et al 2019 ; Gyilbag et al 2021 ; Ragatoa et al 2018 ). Reanalysis and climate models provide spatially gridded, historical and future climatic data, essential for studying long-term trends and potential future scenarios of heat impacts on human health across large spatial domains, aiding public health planning and climate change adaptation strategies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 (13%) of the articles cited in this review utilised reanalysis and climate models to simulate past, present, and future heat-human health relationships. 5 (5%) of studies explored future projections of heat stress, high temperature, relative humidity, heatwaves, and extreme heat on human health (Ermert et al 2012 ; Sylla et al 2018 ; Sarr et al 2019 ; Gyilbag et al 2021 ; Ragatoa et al 2018 ). Reanalysis and climate models provide spatially gridded, historical and future climatic data, essential for studying long-term trends and potential future scenarios of heat impacts on human health across large spatial domains, aiding public health planning and climate change adaptation strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have used high resolution regional climate model simulations to estimate the effects of different greenhouse gas emissions scenarios on future health in tropical Africa. Some studies have used climate projections from the recent Coordinated Regional Climate Downscaling Experiment (CORDEX) program (Sarr et al ( 2019 ), Ragatoa et al ( 2018 ), Sylla et al ( 2018 ), Gyilbag et al 2021 ) and Adeniyi and Oyekola ( 2017 )), for either Representative Concentration Pathway (RCP) greenhouse gas scenarios or global warming scenarios. Other studies have used the COSMO-CLM regional climate model, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…As water mist evaporation contributes to pre-cooling the ambient air before entering air-cooled condensers, it is a reliable, simple and relatively inexpensive way to lower the ambient air temperature and is a potentially effective method to improve chiller efficiency with substantial energy savings [11][12][13][14][15]. Currently, an emerging concern worldwide is the increased frequency of heatwaves, particularly over the last decade, that significantly reduce the efficiency of compressors in air conditioning systems [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the recently released climate hazards group infrared temperature with station (CHIRTS) T-dataset (Verdin et al, 2020) showed a high level of accuracy at the world scale, with CHIRTS daily correlations with observations ranging from 0.7 to 0.9, and very good representation of heat wave trends. Based on these preliminary results some studies used CHIRTS to report on heatwaves trends dynamics across Kenya (Amou et al, 2021) and Tanzania (Gyilbag et al, 2021).…”
mentioning
confidence: 99%